Peluang Penerapan Subsidi Buy the Service (BTS) Bus Rapid Transit (BRT) untuk Meningkatkan Kualitas Pelayanan Angkutan Umum Kota Padang Panjang - Masbiran, Vivi Ukhwatul Khasanah; Yolarita, Elsa; Wiguna, Syapta; Andari, Tania; Afriyanni, Afriyanni; Momon, Momon (Jurnal Bina Praja, 2022)
This study aims to analyze the cost of subsidies and the opportunity to implement Buy the Service (BTS) for Bus Rapid Transit (BRT) in Padang Panjang City. This study uses a quantitative method with a descriptive approach. Primary data collection includes observation and distribution questionnaires with respondents using public and non-public transport users. The information obtained from the distribution of questionnaires is the origin of the destination, characteristics of public transportation behavior, and the willingness to pay of the community towards public transportation modes that follow public transportation service standards. The operational costs of public vehicles are obtained from the survey results of the basic costs of public transportation, which consist of direct and indirect costs. The results of this study formulate 3 (three) main route trajectories scenarios and cost analysis of BTS implementation that meets Minimum Service Standards (SPM). The estimated subsidy cost for implementing BTS in the three main corridors is 10.09 billion, with the highest subsidy cost being in corridor 1. which is 4.41 billion but has a smaller headway than the other two corridors. The results of this study also recommend the need for continuous socialization to the community regarding the ease and convenience of using BRT as well as equalizing perceptions between local governments and operators regarding the mechanism for providing BRT subsidies.